Penerapan Program Pembelajaran Terjemah Al-Qurán (PPTQ) untuk Meningkatkan Penguasaan Mufrodat Perspektif Teori Ivan Pavlov - Okita Fatma Marliana; Faisal Mahmoud Adam I; Zakiyah Arifa (EduInovasi: Journal of Basic Educational Studies, 2025)
The Quran Translation Learning Program (PPTQ) at MA Shirothul Fuqoha' was studied through the perspective of Pavlov's theory which emphasizes stimulus-response association and positive reinforcement and has been proven to significantly improve students' mastery of vocabulary. This qualitative case study research used observation, interviews, documentation, and Miles and Huberman data analysis to describe the planning, implementation, evaluation, and constraints of the program. In planning, the initial steps include analyzing student abilities, class classification, compiling an independent syllabus, and teacher training. The implementation of PPTQ consists of four repetitive stages: (1) the teacher reads the words and meanings, students imitate; (2) the teacher reads the words, students state the meaning; (3) the teacher shows the words, students explain the meaning; and (4) the teacher appoints random students to read the words and meanings. Each addition of vocabulary must go through this cycle, then ends with a closing statement containing the interpretation of the verse. In addition, the morning habituation program, namely reciting the Quran together and giving meaning to each word, is carried out routinely in the school yard. Learning evaluation is divided into formative (written and oral tests at each meeting) and summative (end of semester oral tests witnessed by parents). Teachers' obstacles come from internal factors (teacher competence, double jobs, limited time), students (low enthusiasm, limited ability to read the Qur'an), and institutions (double workload). Some obstacles have been overcome, but some are still in the process of being improved. All graduates of this program are able to translate verses of the Qur'an; some even memorize and interpret them well.